Integrating Eco-Friendly Projects into English for Young Learners: Fostering Creativity and Environmental Awareness: Mengintegrasikan Proyek Ramah Lingkungan dalam Pembelajaran Bahasa Inggris untuk Anak Usia Dini: Menumbuhkan Kreativitas dan Kesadaran Lingkungan - Ria Angraini; Dhani Putra Riyanto; Mulki Yustinto; Sindi Julestri; Dela Vanesa (Gayaku Publisher, 2026)
This study explores the integration of eco-friendly projects into English for Young Learners (EYL) to foster creativity and environmental awareness. Using a qualitative, descriptive-explorative approach, data were collected through observations, interviews, and documentation involving elementary school students and their teachers. The findings show that eco-projects provide authentic contexts for functional English use, encourage creative thinking in planning and implementing projects, and enhance students’ environmental responsibility. Active participation in projects increases motivation, collaboration, and ownership of learning. The study suggests that teachers should utilize environmental issues as learning resources, curriculum developers should incorporate eco-projects into EYL programs, and parents should support environmental practices at home. Overall, eco-friendly project-based learning effectively develops linguistic skills, creativity, and sustainable values in young learners.